Arbitrage in the Term Structure of Interest Rates: a Bayesian Approach - Márcio Poletti Laurini; Armênio Westin Neto (International Econometric Review (IER), 2014)
This work presents an analysis of the presence of arbitrage opportunities in the term structure of interest rates, through the estimation of the affine generalized Nelson-Siegel model with correction for no-arbitrage. We challenge the necessity of the condition of noarbitrage using the Brazilian term structure of interest rates by observing the interbank deposits (DI) contracts traded in the Mercantile and Futures Exchange (BM&FBOVESPA) in Brazil between 2007 and 2009. To verify the necessity of imposing no-arbitrage restrictions, we propose an analysis using Bayesian methods of estimation and testing of this model. We also discuss the estimation procedure in the presence of an irregular maturity structure. Our chosen methodology is especially relevant for emerging markets, where the liquidity of emerging markets varies substantially over time, especially in periods of crises. The results of our analysis indicate that the no-arbitrage corrections are not necessary and that this model is an appropriate specification for this term structure of interest rates.
Keywords: G12; C22; C11; 330; Arbitrage; Term Structure of Interest Rates; Latent Factors; Bayesian Inference; Nelson-Siegel Dynamic Models